2016
DOI: 10.1186/s13722-016-0064-7
|View full text |Cite
|
Sign up to set email alerts
|

Emerging adults in substance misuse intervention: preintervention characteristics and responses to a motivation-enhancing program

Abstract: Background Emerging adulthood is an age of particularly risky behavior. Substance misuse during this phase of life can be the beginning of longer-term problems, making intervention programs particularly important. This study’s purposes were to identify alcohol use profile subgroups, describe the preintervention characteristics of each, and assess how many participants transitioned to lower-risk profiles during the course of the intervention.MethodsWe used latent transition analyses to categorize 1183 people co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…The intervention nonresponders class (59.26%) did not show decreases in drinking at either follow-up timepoint and represent those nonresponsive or resistant to efforts to change their drinking. Similar to prior studies with college (Henson et al, 2015;Mun et al, 2009), dependent (Wikiewitz & Masyn, 2008), or court-ordered (Beadnell et al, 2016) samples, we found heterogeneous subgroups in intervention response. However, our study identified two classes whereas prior studies ranged from three to six classes.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The intervention nonresponders class (59.26%) did not show decreases in drinking at either follow-up timepoint and represent those nonresponsive or resistant to efforts to change their drinking. Similar to prior studies with college (Henson et al, 2015;Mun et al, 2009), dependent (Wikiewitz & Masyn, 2008), or court-ordered (Beadnell et al, 2016) samples, we found heterogeneous subgroups in intervention response. However, our study identified two classes whereas prior studies ranged from three to six classes.…”
Section: Discussionsupporting
confidence: 86%
“…Among college students, multiple distinct groups have been identified, as Henson, Pearson, and Carey (2015) found six subgroups that differed in response to alcohol intervention and Mun, White, and Morgan (2009) identified four subgroups whereby intervention effects were strongest for those with greater problematic drinking at baseline. Among community samples, distinct groups have also been identified, as Witkiewitz and Masyn (2008) revealed three subgroups of drinkers following relapse post-intervention and Beadnell, Crisafulli, Stafford, and Casey (2016) found two low-and two high-risk groups that varied in intervention response. Thus, research supports heterogeneity in intervention response, but to our knowledge, has not identified subgroups of nonstudent emerging adults post-intervention.…”
mentioning
confidence: 99%
“…Burton et al found that a majority of clients switched from high symptom subgroups to a low symptom subgroup. Last, Beadnell et al (2016) identified subgroups of alcohol use among EAs receiving a motivational‐enhancement intervention. Beadnell et al found that clients in the two low‐ risk subgroups of no use and light use, and the high‐risk subgroup of frequent heavy use, were likely to remain from pre‐ to postintervention, whereas those in the high‐risk subgroup of occasional heavy use were likely to switch to the low‐risk subgroups.…”
Section: Latent Subgroup Analyses Of Treatment Effectivenessmentioning
confidence: 99%
“…However, among those who completed substance abuse treatment as well as PFL or standard educational program, there was a significant Age × Program interaction, with PFL showing an advantage relative to standard education for the 40–49 and 50+ age groups but not the 18–29 and 30–39 age groups (Beadnell et al, ). In an additional study (Beadnell, Crisafulli, Stafford, & Casey, ) that specifically examined the short‐term effects of PFL in emerging adults (ages 18–25) in 10 states, the program was shown to help participants transition from high‐risk DUI profiles at baseline to low‐risk DUI profiles at program completion.…”
mentioning
confidence: 99%